The construction of Brazilian Environmental Product Declaration System (Sustainability in Debate, 2017)
Type III ecolabel has been adopted by many countries in the world, especially after the demands ofEuropean countries. The increased adoption of type III ecolabel and elaboration of rules to categorizeproducts in various productive sectors have been observed. Brazil, recently has published anenvironmental product declaration (EPD) program (Programa de Rotulagem tipo III-DAP) regulated bythe National Metrology, Quality and Technology Institute (Instituto Nacional de Metrologia, Qualidade e Tecnologia ”“ INMETRO), also responsible for Brazil’s life cycle analysis program. This article identifiedand analyzed instruments, challenges, limits and possibilities to implement the program proposed byINMETRO for type III ecolabel, based on international experience, SWOT analysis and interviews withindustry actors. It was concluded that INMETRO’s program is recent but aligns well with other programsaround the world, allowing a possible mutual recognition in the future. Moreover, the Brazilian programcan be integrated to other public policies, strengthening its own implementation.